Breast reconstruction with Superior Gluteal Artery Perforator free flap: 8 years of experience. Issue 10 (October 2019) - Zoccali, Giovanni; Mughal, Maleeha; Giwa, Lolade; Roblin, Paul; Farhadi, Jian
Summary: Introduction: The SGAP flap represents an alternative for autologous breast reconstruction when DIEP is not available. In this article, we report eight years of experience in breast reconstruction using SGAP free flap and discuss our results, how our procedures have evolved, the outcomes and complications rates and how to perform this procedure efficiently while managing the challenges inherent to this type of flap. Materials and methods: A retrospective study was conducted from June 2009 and June 2017. Patients requiring SGAP flap breast reconstruction were enrolled. Donor site availability was categorised into 4 classes according to the availability of tissue. An ad hoc outcome scale was created to standardise the results and ensure data comparability. Results: A total of 119 patients were enrolled in the study. We recorded 18 cases of excellent results, 57 good, 30 moderate and 14 poor. Our results show that donor site class impacts complications and patient outcome. The odds ratio analysis demonstrated that the third class donor site has a protective impact on complications and has a direct correlation with good patient outcomes. Conclusions: SGAP flap can provide very good outcomes, and it should be considered as another option when DIEP is not available. Patient selection and efficiency are the keys to achieve optimal results and minimise complications. Although this flap is available for patients with a low BMI, the donor site has to provide enough tissue to achieve symmetry with the contralateral breast and allow a tension-free closure without contour deformity.